Military Responses to the Global Migrant Crisis - Vankovska, Biljana; Kirkova, Rina (Faculty of Philosophy, Skopje, 2018)
The paper aims at a study of the recent trend of increased militarization of border security in the face of mass migratory influx. The theoretical framework of analysis draws on the findings of the theory of civil-military relations, particularly with regard to the concept of ‘core military missions’. The basic premise is that the failure of the liberal interventionism and export of democracy (often by military means or by stirring internal opposition movements towards regime change) has led to catastrophic consequences, which in return hit as a boomerang not only the world interventionist powers but also many other (transitory) states. Among other concerns, the dilemma of the militarization of border control has become an issue of special significance both for international and national security. The renewed military mission of safeguarding the borders from migrant flaws calls for urgent theoretical deliberations and practical solutions.
Keywords: refugees, international migration, core military missions, border control, militarization